Auctions where incomes are private information and preferences (non quasi-linear) are common knowledge - Krishnendu Ghosh Dastidar (Osaka University, Institute of Social and Economic Research (ISER), 2010)
We consider a two good world where an individual i with income mi has utility function u (x, y), where x element of [0, ∞) and y element of 0, 1. We first derive the valuation (maximum price that he is willing to pay for the object) for good y as a function of his income. Then we consider the following problem. Suppose good x is available in a store at a fixed price 1. Good y can be obtained in an auction. In such a situation we show that bidding ones own valuation is an equilibrium in a second-price auction. With risk neutral bidders and high enough incomes we derive the symmetric equilibrium in first-price and all-pay auctions and show that revenue equivalence fails to hold. With risk neutrality we also show that under mild restrictions, the revenue maximising reserve price is zero for all the three auctions and the all-pay auction with zero reserve price fetches the highest expected revenue. With low enough incomes, we show that under some restrictions, bidding ones own valuation is a symmetric equilibrium even for first-price and all-pay auctions. Here also, the expected revenue is the highest with all-pay auctions.
Keywords: D44; 330; Einkommen; Asymmetrische Information; Präferenztheorie; Auktionstheorie; Theorie